REFINEMENT OF MISERITE CRYSTAL STRUCTURE (K1.29□0.21)[CA5.51 M0.493+](SI6(O,OH)15) (SI2O7)(F,OH)2 · 0.25H2O (M = Y, REE, FE, TI, MN, MG, NA) FROM THE DARA-I-PIOZ OCCURRENCE, PAMIR, TAJIKISTAN - Rozhdestvenskaya I.V.; Evdokimov M.D. (My University, 2006)
Miserite is an infrequent alkali Ca-silicate with two types of silicate radicals. The crystal structure of this mineral from carbonatites of the Kipawa Lake deposit, Quebec, Canada. This work, based on the photo method, had until recently remained the only structural study of miserite. Some of its results require refinement. Electron microprobe analysis yielded the following chemical composition (wt %): SiO2 50.61, TiO2 0.16, Al2O3 0.05, FeO 0.32, MgO 0.08, CaO 32.66, MnO 0.24, Na 2O 0.06, K2O 6.59, Y2O3 2.11, La2O3 0.09, Ce2O3 1.06, Pr2O3 0.66, Nd2O3 1.36, total (REE + Y)2O3 5.28, F 1.1, L.O.I. 6.8, H2O 5.7, –O=F2 0.46, total 102.85.
Keywords: Miserite